ANALISIS DAMPAK PANDEMI COVID19 TERHADAP KINERJA KEUANGAN PT GARUDA INDONESIA (Tbk) - Elisabeth Suban; UmmyKalsum; Andi Runis Makkulau (Sigma: Journal of Economic and Business, 2022)
This article is the result of research that analyzes the impact of the Covid-19 pandemic on the financial performance of PT Garuda Indonesia in 2017-2021. Financial performance measurement technique which consists of several financial ratios to measure liquidity, activity, solvency and profitability. This study aims to describe the financial performance of PT. Garuda Indonesia Tbk. during the period 2017-2021. The results of this study indicate that the analysis of the impact of the Covid-19 pandemic on PT Garuda Indonesia experienced a decrease in the Current Ratio which caused a decrease. Analysis of the Debt to Asset Ratio at PT Garuda Indonesia that the Covid-19 pandemic has the impact of changes that cause increased financial performance. Analysis of the impact of the Covid-19 pandemic on PT Garuda Indonesia has decreased on Return on Investment. Analysis of the impact of the Covid-19 pandemic on PT Garuda Indonesia experienced a decline in Net Profit Margin. Analysis of the impact of the Covid-19 pandemic on PT Garuda Indonesia experienced a decline in Fixed Asset Turnover.